Radial Versus Femoral Access for Rotational Atherectomy: A UK Observational Study of 8622 Patients. (December 2017) - Watt, Jonathan; Austin, David; Mackay, Daniel; Nolan, James; Oldroyd, Keith G.
Abstract : Background—: Rotational atherectomy (RA) is an important interventional tool for heavily calcified coronary lesions. We compared the early clinical outcomes in patients undergoing RA using radial or femoral access. Methods and Results—: We identified all patients in England and Wales who underwent RA between January 1, 2005, and March 31, 2014. Eight thousand six hundred twenty-two RA cases (3069 radial and 5553 femoral) were included in the analysis. The study primary outcome was 30-day mortality. Propensity scores were calculated to determine the factors associated with treatment assignment to radial or femoral access. Multivariable logistic regression analysis, using the calculated propensity scores, was performed. Thirty-day mortality was 2.2% in the radial and 2.3% in the femoral group ( P =0.76). Radial access was associated with equivalent 30-day mortality (adjusted odds ratio [OR], 1.06; 95% confidence interval [CI], 0.77–1.46; P =0.71), procedural success (OR, 1.04; 95% CI, 0.84–1.29; P =0.73), major adverse cardiac and cerebrovascular events (OR, 1.05; 95% CI, 0.80–1.38; P =0.72), and net adverse clinical events (OR, 0.90; 95% CI, 0.71–1.15; P =0.41), but lower rates of in-hospital major bleeding (OR, 0.62; 95% CI, 0.40–0.98; P =0.04) and major access site complications (OR, 0.05; 95% CI, 0.01–0.38; P =0.004), compared with femoral access. Conclusions—: In this large real-world study of patients undergoing RA, radial access was associated with equivalent 30-day mortality and procedural success, but reduced major bleeding and access site complications, compared with femoral access. Abstract : Supplemental Digital Content is available in the text.